Oblique lumbar interbody fusion—address to an anatomical challenge: a case report - Meng, Yuxin; Gao, Shangju; Meng, Fantao; Li, Wenyi; Niu, Yanwang; Wei, Jingchao (Frontiers in Surgery, 2025)
Oblique lumbar interbody fusion (OLIF) is a minimally invasive technique for the treatment of degenerative diseases of the lumbar spine, and the left operative window is always used to avoid the inferior vena cava (IVC). However, in cases with anatomical variations—particularly vascular anomalies, which most significantly impact surgical approaches—the right retroperitoneal approach may serve as a preferable alternative. This case report describes a 59-year-old man with lumbar instability and a rare left-sided IVC who underwent OLIF via a right approach. Preoperative imaging of this patient showed an isolated left IVC. The procedure was performed through a right-sided surgical corridor bounded medially by the abdominal aorta(AA) and laterally by the right psoas major muscle. The approach was supplemented with lateral screw-rod instrumentation to maintain stability. The patient's neurological function improved significantly after surgery, and the surgical approach proved to be feasible while maintaining biomechanical stability while avoiding vascular risk. This case highlights the importance of vascular evaluation before OLIF. Especially for the rare left-sided IVC, OLIF via right approach can effectively improve safety.